Optimasi Proses Pembuatan Karbon Aktif dari Ampas Bubuk Kopi Menggunakan Aktivator ZnCl2 - Rasdiansyah Rasdiansyah; Darmadi Darmadi; Muhammad Dani Supardan (Jurnal Teknologi dan Industri Pertanian Indonesia, 2014)
Activated carbon can be manufactured from a variety source materials containing element carbon. Dregs of coffee grounds is one of abundant and promising activated carbon raw materials. This study was conducted to assess optimization process of activated carbon production from dregs of coffee grounds by using ZnCl2 as an activator. The optimization process is performed by using Response Surface Method to optimize factors that affected quality of the activated carbon using Box-Behnken design. The factors used were carbonation temperature (T) with a level of 400 oC, 500 oC and 600 °C; concentration of ZnCl2 (K) with a level of 30%, 40%, 50%; and mass ratio of ZnCl2 to activated carbon with level of 2:1, 3:1 and 4:1. A second order regression model of iodine absorption of activated carbon was Y = 626,2 - 36,5T + 28,6K - 36,5R + 31,2T2 + 47,1K2 - 0,5R2 - 19,0TK + 15,9TR + 101,5KR. Results of optimization process showed that optimum iodine absorption of 799.659 mg/g was obtained at the following conditions, i.e. carbonation temperature of 400 oC, ZnCl2 concentration of 30% and mass ratio of ZnCl2 to activated carbon of 2:1.